Emotional Intelligence, Self-Regulation, Smartphone Addiction: Which Relationship With Student Well-Being and Quality of Life? - Mascia, Maria Lidia; Agus, Mirian; Penna, Maria Pietronilla (Frontiers in Psychology, 2020)
This study states the importance to analyse factors that contribute to students’ well-being, as the result of many factors that might affect their quality of life. Literature shows as, among these factors, emotional intelligence and self-regulation control could have a central role in influencing adolescents' psychological and scholastic well-being. Indeed, although technologies represent a fundamental aspect of adolescents’ life, an addictive use of smartphone is today present and it might touch the individual well-being and quality of life. So, this work investigates also the role of the smartphone use regarding these constructs. 215 Italian students attending a Middle School, participated in the study. By the application of Partial Least Square Structural Equation Model (PLS_SEM), the findings confirm that self-regulation has an influence on students’ quality of life, but its role changes in relation of the smartphone addiction. In conclusion, we can affirm the relevance of relationship between self-regulation and smartphone addiction, in order to educate students to be aware about the time spent using smartphone; it is important to enhance emotional intelligence and, over all, self-regulation, to support the students’ well-being and quality of life in adolescences at school.